Modelling the impact of Global Change on the hydrological system of the Aral Sea basin - Beek, Tim aus der; Voß, F.; Flörke, Martina (Physics and chemistry of the earth, 2011)
During the last decades the Aral Sea basin has suffered an enormous depletion of water resources within its lakes and rivers with consequences for society, economy, and nature. Within this model study, Global Change impacts on the Amu Darya and Syr Darya rivers, as well as on the Aral Sea itself, are being analysed for the period 1958-2002. In a first step, a multi-annual data base on crop specific irrigated areas has been set-up, which has then been integrated in the hydrology and water use model WaterGAP3. As a second step, anthropogenic water abstractions have been calculated, which were then assimilated in the simulation of river runoff of the Amu Darya and Syr Darya. The last step includes the simulation of the water balance of the Aral Sea, by taking into account modelled river inflow. Within WaterGAP3, the water use module has been switched on and off to separate the impacts of Climate and Global Change (i.e. water abstractions). Irrigation water abstractions are very well represented by WaterGAP3 and lie within the range of reported values. Modelled river discharge also shows a good fit to observed data, whereas phases are in sync but volumes are slightly overestimated. Simulated volumes of the Aral Sea itself are well reflected by the model, though results for the period 1990-2002 are too high. In this study, the Climate Change impacts are much smaller (14%) than the water use impacts (86%) on the shrinkage of the Aral Sea. Finally, an outlook on potential scenario model studies is given, which could analyse the different strategies of mitigation and adaptation of Global Change in the Aral Sea basin.
Gesehen am 10.03.2022